Strategies for Improving Arabic Speaking Skills in Islamic Boarding Schools - Mizan, Khairul; Musdalipa, Musdalipa; Mubaligh, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2024)
Learning Arabic shows serious attention to speaking skills, because many students do not speak fluently even though they have studied from MI to university. Therefore, the need for appropriate strategies in learning. This research aims to explore the strategies of the An-Nur Tangkit Islamic boarding school in improving speaking skills. This research is a qualitative descriptive research with a case study type. Data was collected through observation, interviews and documentation. Then analyzed using Mills and Huberman. The research results show that the An-Nur Tangkit Islamic Boarding School is an educational institution that is committed to using Arabic and English as the languages ​​of daily communication. The strategies used are: a) providing vocabulary every Monday, Wednesday, Thursday, Saturday and Sunday after morning prayers; b) conversation practice every Tuesday and Friday for 30 minutes with a theme according to the vocabulary given previously; c) requires the use of direct methods in language-oriented learning; d) speech practice every Tuesday and Thursday; e) creating a language environment, namely the use of Arabic and English and prohibiting the use of Indonesian, let alone regional languages; f) holding competitions between man students and female students to create a competitive spirit for student in language. So it can be concluded that these strategies are the right strategies to improve speaking skills for students.